Adolescent Female's Perception of Body Image as a Social Media User - Hutagalung, Mega Julia; Daulay, Annisa Arrumaisyah (Universitas Muhammadiyah Ponorogo, 2024)
Adolescence is a transition period from childhood to adulthood. In this case, it is related to body image and is a problem that is still felt, especially by young women. Body image is an individual’s overall perception of his body, which includes thoughts and perceptions of his body. One of the factors that influences body image is social media. Through social media, young women learn a lot of information about body standards that are considered ideal. The type of research is descriptive qualitative research. The research location took place in Pancuran Dewa sub-district, Sibolga City. The sampling technique uses purposive sampling and also the data analysis technique uses domain analysis which is carried out starting from reducing data, presenting data, and drawing conclusions. This research aims to provide insight into how social media influences the perceptions of young women and encourage media users, especially young women, to be smarter and more critical in consuming media and knowing how young women feel about their body image as social media users